2018
DOI: 10.1016/j.appet.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and laboratory eating behavior in adolescent girls at risk for type 2 diabetes

Abstract: Mindfulness-based intervention has become increasingly popular to address disinhibited eating in obesity and type 2 diabetes (T2D). Theoretically, present-moment attention promotes the ability to recognize and respond to internal hunger cues and to differentiate physiological hunger from other stimuli. Yet, there is limited research describing the relationship of mindfulness with disinhibited eating patterns in adolescents. In this study, we evaluated the relationship of dispositional mindfulness to laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 62 publications
(80 reference statements)
1
13
0
Order By: Relevance
“…Five studies were related to prevention and were conducted using non-clinical (non-eating disordered) adolescent cohorts. Five studies were conducted among high risk cohorts of overweight and obese adolescents [46][47][48][49][50], and two were conducted among girls with LOC eating or binge eating [51,52]. Additionally, three studies were conducted among adolescents with restrictive eating disorders [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies were related to prevention and were conducted using non-clinical (non-eating disordered) adolescent cohorts. Five studies were conducted among high risk cohorts of overweight and obese adolescents [46][47][48][49][50], and two were conducted among girls with LOC eating or binge eating [51,52]. Additionally, three studies were conducted among adolescents with restrictive eating disorders [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 13 of the 15 studies reported mild positive effects of mindfulness [43][44][45][46][47][48][50][51][52][53][54][55]61,62]. Two of these studies [43,51] found mindfulness was associated with reduced weight/shape concerns and dietary restraint among adolescent girls, while others found it to be associated with decreased BMI [48], EAH [46], and binge eating [47]. Mindfulness-based DBT interventions were also found to reduce ED psychopathology in four studies conducted among clinical cohorts of adolesents with eating disorders [52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations